Turning Eight Family Homes Into Interactive, Pervasive Playgrounds During the COVID-19 Pandemic Lockdown - Matjeka, Louise Petersen; Svanæs, Dag; Wang, Alf Inge (Frontiers in Computer Science, 2022)
This paper presents an evaluation study of how eighth families adopted, played and experienced a movement-based game system of analogue and digital technologies in their homes during a pandemic lockdown. The COVID-19 pandemic locked down many countries and grounded people in their homes with social and physical implications. A game system consisting of simple, tangible technologies with modular components was designed to meet these needs. The game system was developed for the players to set up in their homes easily and, therefore, should not depend on screens or extensive physical installations. The game system comprises simple, tangible technologies such as light and music cubes, a simple mobile robot, card game challenges, and a suite of mini-games combining the elements in a variety of playful experiences. Using the technology probes methodology, the game system was packed into a suitcase and evaluated by eight families that played the game in their homes, video-recorded their sessions, wrote a final report and were (informally) interviewed afterwards. The data set presents how the families turned their ordinary everyday spaces into interactive, pervasive playgrounds encouraging social and bodily exploration and play. Furthermore, the study shows how bodily movement and social play can be promoted through different technologies that stimulate various bodily senses and incorporate them through the different game and play structures into their everyday living environments. The findings resulted in four design implications to aid designers and researchers in future work on movement-based game systems and interactive, pervasive playground design. These design implications accommodate social and bodily activities in ordinary places otherwise not pre-allocated for play or game activities.